Synthesis of barium ferrite using barite ore (International Seven Journal of Multidisciplinary, 2024)
Ferrites, with formula MFe12O19, where M is one of the elements Ba, Sr or Pb, have the crystal structure of magnetoplumbite. One of the most industrially used magnetic materials is barium ferrite (BaFe12O19), with properties such as: high resistivity, high coercivity, relatively low magnetic saturation, etc. In this work, the synthesis of barium hexaferrite (BaFe12O19) was carried out from a baryte mineral (BaSO4) and ≥98% nanohydrated iron nitrate (Fe(NO3)3*9H2O), in a temperature range of 220-250°C. Characterization was carried out using X-ray diffraction (XRD) to determine the crystalline phases present and scanning electron microscopy (SEM) to observe the microstructure and particle size of the barium ferrite.